Скандал Ф. Достоевского и М. Бахтина - ТОРОП, ПЕЭТЕР (SlavVaria, 2021)
Scandal of F. Dostoevsky and M. Bakhtin. Article is dedicated to analysis of relations between Dostoevsky’s artistic works, journalism and Bakhtin’s books about Dostoevsky poetics on the basis of frequency of word scandal. Scandal as word of Dostoevsky artistic language (object language), as element of analytical language of Dostoevsky as journalist (autometalanguage) and as notion for analysis of Dostoevsky poetics in the book of Bakhtin (metalanguage) raises methodological question about flexibility of metalanguage in situations where a same word can function simultaneously on all levels of description of research object.